TI_GERICHTE 12.2019.13 vom 9. April 2020 , Contratto di appalto - resciaaione del contratto da parte dell'appaltatore - TI Tribunale d'appello (2020)
Contratto di appalto - resciaaione del contratto da parte dell'appaltatore